2022
DOI: 10.3390/antiox11061101
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin Protects against H2O2-Induced Oxidative Damage in SH-SY5Y Cells by Improving Mitochondrial Function

Abstract: Oxidative stress plays a critical role in the pathogenesis of various neurodegenerative diseases. Increasing evidence suggests the association of mitochondrial abnormalities with oxidative stress-related neural damage. Silibinin, a natural flavonol compound isolated from Silybum marianum, exhibits multiple biological activities. The present study investigated the effects of silibinin on H2O2-induced oxidative stress in human neuroblastoma SH-SY5Y cells. Exposure to H2O2 (750 µM) reduced the viability of SH-SY5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Conversely, silybin supplementation markedly normalizes mitochondrial dynamic imbalance under PQ challenge. An in vitro study also suggested that silybin treatment protects human neuroblastoma SH-SY5Y cells from H 2 O 2 -induced mitochondrial damage by regulating OPA1 and Drp1 protein expression [ 57 ]. Collectively, silybin supplementation protected against PQ-induced liver injury in piglets by improving mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, silybin supplementation markedly normalizes mitochondrial dynamic imbalance under PQ challenge. An in vitro study also suggested that silybin treatment protects human neuroblastoma SH-SY5Y cells from H 2 O 2 -induced mitochondrial damage by regulating OPA1 and Drp1 protein expression [ 57 ]. Collectively, silybin supplementation protected against PQ-induced liver injury in piglets by improving mitochondrial functions.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological activity associated with flavonoids in H. rhamnoides encompasses antioxidant, hypoglycemic, hypolipidemic, and antitumor effects. [13,14,26] The current study aimed to isolate and characterize three new kaempferol derivatives from the seed residue of H. rhamnoides, a plant that is regarded as industrial waste. These derivatives each incorporate four sugar moieties that share the core nuclear structure of kaempferol, which is essential for their antioxidative potential.…”
Section: Discussionmentioning
confidence: 99%
“…The SH-SY5Y cells were cultured in 6-well dishes at 5 × 10 5 cells/well density and incubated overnight. Then, cells were treated with 20 µM incubated samples aged alone or in the presence of 200 µM catechols and incubated for 6 h. Cells treated with 750 µM H 2 O 2 70 were used as a positive control. After incubation, 5 µM DCFDA was added to each Petri dish, and cells were incubated for an additional 30 min at 37 °C.…”
Section: Methodsmentioning
confidence: 99%